Design Analysis of Hydraulic Lifter Spreader Assy LRT Using Finite Element Method - Ampala Khoryanton; Gutomo Gutomo; Sugeng Irianto; Farikah Tono Putri; Ahmad Hamim S (Jurnal POLIMESIN, 2023)
Spreader Assy is an integral part of the Jabodebek LRT train delivery. This part serves as an elevating device for the carriage. The installation of the spreader assembly to the train body poses a hazard to operators and work instruments, is too lengthy, and does not adhere to the Standard Operating Procedure (SOP). This issue is due to the implementation of the spreader assembly, which is still supported by crowbars, wood, and an iron plate. This study's objective is to analyze the design of the hydraulic lifter for the operator's convenience and safety when installing the spreader assembly. Hydraulic jack, base plate, and lifting plate are the primary components of this instrument. Based on FEA analysis, the stress that occurs in the hydraulic lifter construction after receiving the spreader assy load of 225.18 kg is between 3,312,239 N/m2 and 6,624,476 N/m2, whereas the yield strength of the SS400 material is 250,000,000 N/m2 because the stress is greater than the yield strength of the material. Since the maximum value is still well below the material's yield stress, it can be concluded that the hydraulic lifter construction can safely support the burden of the spreader assembly